2015
DOI: 10.1016/j.mtcomm.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent dynamic mechanical properties of Kevlar to failure: Structural correlations and comparisons to other polymers

Abstract: The processing of Kevlar to certain strengths by hot-drawing can benefit by quantitative understanding of the correlation between structural and mechanical properties during the pre-drawing process. Here, we use a novel continuous dynamic analysis (CDA) to monitor the evolution in storage modulus and loss factor of Kevlar 49 fibers as a function of strain via a quasi-static tensile test. Unlike traditional dynamic mechanical analysis, CDA allows the tracking of straindependent mechanical properties until failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 10 publications
(24 reference statements)
1
28
0
Order By: Relevance
“…The fibers surfaces in the reference mAr (Figure a) and pAr (Figure b) fabrics is uneven with visible lengthwise cracks. Aramids fibers have a fibrillar and pleated structure with bundles . There are no significant changes in topography after corona discharge treatment for mAr fabric.…”
Section: Resultsmentioning
confidence: 95%
“…The fibers surfaces in the reference mAr (Figure a) and pAr (Figure b) fabrics is uneven with visible lengthwise cracks. Aramids fibers have a fibrillar and pleated structure with bundles . There are no significant changes in topography after corona discharge treatment for mAr fabric.…”
Section: Resultsmentioning
confidence: 95%
“…22,[35][36][37] This clearly is to be expected from a rule of mixtures analysis 4,7,13,[23][24][25][26][27] owing to the much higher Young's modulus of the filler. 1,3,5,8,10,22,[28][29][30][31] Fewer studies have shown the opposite effect, that of a reduction in Young's modulus.…”
Section: Introductionmentioning
confidence: 85%
“…Most studies on nanocomposites fillers reveal a progressive increase in modulus with increasing reinforcement volume fractions; examples of studies in polymers include claybased nanocomposites, [12][13][14]19,20 microscale ceramic TPs and needles, 15,16,21 graphene, 17,22 carbon nanotubes, 13,18,[23][24][25][26][27] carbon black, 3,8,10,19,20,22,[28][29][30][31] glass fibers, 3,8,10,21,32-34 and others. 22,[35][36][37] This clearly is to be expected from a rule of mixtures analysis 4,7,13,[23][24][25][26][27] owing to the much higher Young's modulus of the filler.…”
Section: Introductionmentioning
confidence: 99%
“…Here, using nanorods (NRs) and tetrapod quantum dots (tQDs) in both electrospun fibers and solvent-cast films, we study the effect of increasing nanoparticle branching on the Young's modulus of a common structural elastomer, poly(styrene block−ethylene−butylene block−styrene) (SEBS) (20). We chose SEBS since it is a widely used structural copolymer, has a 40% phase (ethylene−butylene) of similar chemical makeup as our nanoparticle surface ligands (although it is incompatible with 60% of the polymer, the polystyrene (PS) phase), and is amorphous, allowing for improved intercalation with the nanoparticles.…”
mentioning
confidence: 99%